Literary Anthropology : a new interdisciplinary approach to people, signs and literature. - Poyatos, Fernando (John Benjamins Pub. Co., 1988)
The traditional gulf between the theory and practice of literature and the various areas subjoined under anthropology has hindered the development of some very fruitful perspectives in the realm of poetics and the general theory of literature (particularly in its narrative forms). Poyatos' initial idea of literary anthropology as the study of people and their cultural manifestations through their national literatures - without doubt the richest source of documentation of human life-styles and the most advanced form of our projection in time and space and of communicating with contemporary and.